Problems of the Implementation of Diversion in the Case of Children who Use Narcotics in the Police - Jenitasari, Silviyanica; Maharani, Deswita; Maulana, Rizki; Dimyati, Agus; Sutrisno, Anom (International Journal of Social Service and Research, 2025)
The Indonesian Government's policy in dealing with drug abuse cases as stated in Law No. 35/2009 on Narcotics, basically still categorizes drug abuse as a criminal act, with the threat of criminal punishment regardless of the age of the perpetrator. Although the law applies a double track system, namely the imposition of prison sentences that can be accompanied by rehabilitation measures. In particular, in handling cases of children involved in drug abuse, Law No. 11/2012 on the Juvenile Criminal Justice System mandates that case resolution must prioritize diversion efforts. The main reason for the implementation of diversion is in line with the philosophy of the juvenile criminal justice system, which focuses on the protection and rehabilitation of children who commit criminal offenses. The methodology used in the preparation of this scientific work is descriptive analytical, by describing the problems found, then conducting a study and analysis of them based on primary, secondary and tertiary legal materials. The approach used is normative juridical, which is an approach by examining and analyzing secondary data related to the law. The results showed that in the implementation of diversion for children who abuse narcotics, investigators are required to ask for consideration or input from Community Supervisors shortly after a criminal offense report or complaint is received. Police officers have a goal to resolve cases through diversion mechanisms, so that children who are perpetrators of narcotics abuse are not sentenced to criminal penalties.